Effervescent ferrate(VI)-based tablets as an effective means for removal SARS-CoV-2 RNA, pharmaceuticals and resistant bacteria from wastewater - Butor Škulcová, Andrea; Tamášová, Katarína; Vojs Staňová, Andrea; Bírošová, Lucia; Krahulcová, Monika; Gál, Miroslav; Konečná, Barbora; Janíková, Monika; Celec, Peter; Grabicová, Kateřina; Grabic, Roman; Filip, Jan; et al. (Journal of water process engineering, 2021)
Waterborne pathogens including viruses, bacteria and micropollutants secreted from population can spread through the sewerage system. In this study, the efficiency of unique effervescent ferrate-based tablets was evaluated for total RNA and DNA removal, disinfection and degradation of micropollutants in hospital wastewater. For the purpose of testing, proposed tablets (based on citric acid or sodium dihydrogen phosphate) were used for various types of hospital wastewater with specific biological and chemical contamination. Total RNA destruction efficiency using tablets was 70-100% depending on the type of acidic component. DNA destruction efficiency was lower on the level 51-94% depending on the type of acidic component. In addition, our study confirms that effervescent ferrate-based tablets are able to efficiently remove of SARS-CoV-2 RNA from wastewater. Degradation of often detected micropollutants (antiepileptic, antidepressant, antihistamine, hypertensive and their metabolites) was dependent on the type of detected pharmaceuticals and on the acidic component used. Sodium dihydrogen phosphate based tablet appeared to be more effective than citric acid based tablet and removed some pharmaceuticals with efficiency higher than 97%. Last but not least, the disinfection ability was also verified. Tableted ferrates were confirmed to be an effective disinfectant and no resistant microorganisms were observed after treatment. Total and antibiotic resistant bacteria (coliforms and enterococci) were determined by cultivation on diagnostic selective agar growth media.
Keywords: Pharmaceuticals; Antibiotic resistant bacteria; Wastewater treatment; Ferrate(VI); SARS-CoV-2